CdSe based nanowires for the photocatalytic production of hydrogen gas - Abdullah, Ilyaas (Department of Chemical Engineering, 2019)
Photocatalytic production of hydrogen was investigated towards achieving a decarbonized supply of hydrogen gas for clean energy conversion technologies such as the proton exchange membrane fuel cell (PEMFC). This study uses a template-directed electrodeposition technique to synthesize multi-segmented CdSe based nanowires for use as a photocatalyst device for hydrogen production. CdSe, Ni, Au and Pt nanowires were successfully synthesized with dimensions ranging from 100 nm to 350 nm in diameter and up to 10 µm long. The CdSe stoichiometry was not easily controlled despite following literature protocols and requires a more systematic investigation. The electrodeposition of Ni nanowires was found to be most effective with very few problems encountered. Improvements in the morphology of Au and Pt nanowires were made by using a constant current as opposed to constant potential electrodeposition techniques. Multi-segmented nanowire devices were prepared with nanowires left embedded in a porous anodized aluminium oxide (AAO) template. Polymer PEDOT: PSS and noble metal Pt was used as an anode and cathode electrocatalyst materials respectively. A prototype photocatalytic testing system was set-up using a 1600 W xenon arc lamp as a light source, an in-house made photoreactor as the device holder, and a mass spectrometer for online gas detection measuring ionic currents of evolved species. The set-up was able to successfully detect hydrogen evolved during the tests but does require further development if more complete photocatalytic testing is to be conducted in future. Photocatalytic hydrogen production from the irradiated devices was inconclusive, but hydrogen detection from devices was observed in an 80 % MeOH solution with no irradiation. Through these tests it was learned that photocatalytic activity needs to be differentiated from regular catalytic activity. This is particularly the case if testing is conducted in organic media and if the photocatalytic phenomena is to be properly isolated and understood correctly